2015
DOI: 10.1097/tp.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Kidney Transplant Recipients From Older Living Donors

Abstract: As use of older kidney donors increases, overall survival among kidney transplant recipients from older living donors was similar to or better than SCD recipients, better than ECD recipients, but worse than younger LD recipients. With increasing kidney donation from older adults to alleviate profound organ shortages, the use of older kidney donors appears to be an equivalent or beneficial alternative to awaiting deceased donor kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 16 publications
1
36
0
1
Order By: Relevance
“…Routine use of older living donors is increasing in clinical practice and organs from older donors have been repeatedly shown to have worse outcomes in LDKT but remains comparatively better than standard, young deceased donor organs (19). In particular, DGF rates above 5% are seen with donors above the age of 60, which is well above the recent overall DGF rate of 2.75% for LDKT reported in the SRTR Annual report (20).…”
Section: Discussionmentioning
confidence: 99%
“…Routine use of older living donors is increasing in clinical practice and organs from older donors have been repeatedly shown to have worse outcomes in LDKT but remains comparatively better than standard, young deceased donor organs (19). In particular, DGF rates above 5% are seen with donors above the age of 60, which is well above the recent overall DGF rate of 2.75% for LDKT reported in the SRTR Annual report (20).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Studies have shown kidneys from >60-years-old donors to have donors. 11,12 Studies have shown kidneys from >60-years-old donors to have donors.…”
Section: Discussionmentioning
confidence: 99%
“…Expectedly, attrition was significant in the >65-years-old cohort long-term. (7) Proteinuria 54 (14) 76 (6) Hyperlipidemia 53 (11) 73 (7) ESRD 56 (11) 84 (4) TA B L E 2 (Continued) (7) Proteinuria 54 (14) 76 (6) Hyperlipidemia 53 (11) 73 (7) ESRD 56 (11) 84 (4) TA B L E 2 (Continued)…”
Section: Characteristics Of Donors >65-years-oldmentioning
confidence: 99%
“…An alternative would be to pursue living donor transplantation from older donors such as their spouses or peers. Several studies have shown that recipients of kidneys from older living donors have reasonable outcomes[41-43]. Englum et al[41] studied 250827 patients based on UNOS data who received a kidney transplant, of which 92646 were LD kidneys and 4186 from donors aged ≥ 60 years.…”
Section: Which Type Of Kidney Is Best?mentioning
confidence: 99%
“…Several studies have shown that recipients of kidneys from older living donors have reasonable outcomes[41-43]. Englum et al[41] studied 250827 patients based on UNOS data who received a kidney transplant, of which 92646 were LD kidneys and 4186 from donors aged ≥ 60 years. Not surprisingly, graft and patient survivals of patients who received a kidney from an older LD were worse compared to those who received a kidney from a younger LD.…”
Section: Which Type Of Kidney Is Best?mentioning
confidence: 99%